Genetic variance of transforming growth factor β2 gene in conotruncal heart defects - Chen, Yu; Zhang, Rui; Xie, Jun; Li, Yajiao; Shi, Shaoqing; Qian, Hong; Yan, Zhiguo; Rao, Li (Biomarkers, 2017)
Objective: The aim of this study was to evaluate the association between two haplotype-tag single nucleotide polymorphisms (SNPs) (rs6658835 and rs10495098) of TGF-β2 and conotruncal heart defects (CTDs). Methods: Two polymorphisms of TGF-β2 gene were genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) from 259 CTDs patients and 310 control subjects. Results: The association between SNP rs6658835 in TGF-β2 and CTDs has been found. The frequency of G allele in CTDs patients was significantly higher than that in control subjects (52.7% versus 40.3%, p < 0.001, OR =1.649). Conclusion: TGF-β2 gene polymorphisms may serve as a novel genetic marker for the risk of CTDs.